LE SUBLIME EST EN BAS: The marinas in the paintings of Lucas Arruda and immanence in the work of Georges Didi-Huberman (Palíndromo, 2026)
This research investigates paintings from the exhibition Eclipse (2025), by the artist Lucas Arruda, through their possible association with certain theoretical keys related to French theoretical thought, mainly his theory of art recent. It seeks to interrogate landscape paintings, focusing on marinas painted by Arruda, based on certain epistemological returns made in the work of, among others, Georges Didi-Huberman. This includes the notion of the sublime in the graphic and poetic production of Victor Hugo, as well as the notion of immanence apprehended from Lucretius' philosophical poem De rerum natura. More than question such artwork in the face of different theoretical references, the objective is to question the artist's paintings in their cleavage, questioning whether his poetics of the sublime is, at the same time, a painting of immanence, and whether such a relationship is pertinent to be placed in the field of art theory and history.